Analisis Perbandingan Kinerja Protokol Transport Layer Pada Lalu Lintas Data VIOP dan IPTV - Yuza Reswan; Dedy Agung Prabowo (Universitas Sriwijaya, 2017)
AbstractOne of the use of VOIP and IPTV technology that is increasingly used as a communication application on the internet are video call and video streaming, so when the data required a reliable and fast protocol performance in the process of delivery. The problem of the research is analyzing the performance of layer transport protocol in VOIP and IPTV data traffic. The objective of the research is to know the advantages and disadvantages of VOIP and IPTV data traffic and it is useful to contribute to the development of transport layer protocols in VOIP and IPTV data traffic in the future. This research is conducted independently without related to place and time. This reasearch uses SoftPerfect network Protocol Analyzer software. SoftPerfect network Protocol Analyzer is used to compare the performance of transport layer protocols of TCP, UDP, SCTV based on six parameters using different LAN and Wireless cable, test time, and sharing time. The method used in this research is based on the research approach. The results of this study indicate that SCTV protocol is a protocol that has good performance in VOIP and IPTV data traffic with TCP and UDP protocol.Keywords : Analysis, Performance, TCP, UDP, SCTP, VOIP, IPTV